REPRESENTATIONS OF “BASIC’ LIBERTY” IN THE CONTEXT OF AGONICAL LIBERALISM - Pankovskij, Anatolij (Politologija, 2015)
The opposition of negative and positive liberty the way it is presented in Isaiah Berlins essay “Two Concepts of Liberty” may be regarded as a pivotal question of liberal thought, although many liberal theorists doubts the adequacy of the difference between positive and negative liberty offered by Berlin. A standard approach suggests that liberty acts as a factor to which all basic human rights and freedoms can be reduced. Berlin aims to undermine this widely spread assumption of the liberal theory insisting on an incompatibility of liberties considered in their extremes. It is due to this reason that John Gray tags Berlins’ liberalism as “agonical”, that is, presupposing incompatibility and conflict of basic values. The following interpretation answers Berlins views the best: 1. Negative liberty is neither the exclusive nor the most precise symbolic representation of “basic liberty”. On the contrary, “basic liberty”, choice as such, is represented on a two-way basis, namely, positive and negative. 2. The meaning of the notion “liberty” is always of high priority (historically, it is almost invariable) and is defined through the problem of limits of submission and compulsion. In other words, this meaning is defined via agonical incompatibility/incommensurability of positive and negative liberty – liberty as authority and liberty as disobedience. 3. The differentiation of the notions of negative and positive liberty would be appropriate as an operation to reveal some conceptual limits. If introduced, this distinction would not mean all liberties can, or must, be plotted out between the negative and positive departments, although in many cases liberties may be analyzed in their negative and positive aspects. 4. Supporting the relevance of protecting negative liberty, the right of nonintervention, Berlin also maintains the inevitable need for restricting the limits of choice. Such manifests run counter to liberal theories, which pledge unlimited expansion of rights and freedoms for all. 5. The so-called “basic” freedom is a tacit, but nevertheless, leading concept of Berlins philosophy. The theoretic directive that provides substantiation of “basic” liberty of a human being involves a plurality of values, equally finite, hence infeasibility of a single standard for their substantiation. Therefore, “basic” liberty may be described as a capability of a human being to act in accordance with free will, that is, without the basic morality, which governs the choice. This choice, often referred to as radical choice, or the one that is not based on sense, makes the essence of our social and political life. The problem of pluralistic substantiation of liberalism is for the most part due to limitations of universality claims of liberalism. Meanwhile, Berlins agonical liberalism is not so much a set of principles for building a liberal society as a critical theory that simultaneously acts as a defense strategy to protect liberal ideals. In this case the principle of universalism suggests that an “acceptable” or “normal” society is the one in which at least a few moral principles are considered universal (not contextual or local). Furthermore, an “acceptable” society allows a plurality of views and regards the social conflict as an accomplished fact, which should be mitigated rather than factored out.